Dataset of root morphology and suberin-related traits in two tropical forage species - Camila Ramirez; Javier Eduardo Lara; Mayorga Cobos, Mildred Julieth; Pascual Madera Doria; Ruiz Hurtado, Andres Felipe; Madera Doria, Yaira Yulieth; Cardoso Arango, Juan Andres (2025)
Soil organic carbon (SOC) sequestration through vigorous and deep root systems is a promising strategy to mitigate the accumulation of greenhouse gases. The presence of carbon compounds with low decomposition rates, such as suberin, is another root trait that can contribute to this process. Forage grasses exhibit a high capacity for SOC sequestration because they develop abundant and deep root systems and allocate a substantial proportion of their photoassimilates to belowground organs. Urochloa humidicola is an ideal species in the context of climate change adaptation due to its strong tolerance to abiotic stresses such as drought, waterlogging, low soil fertility, and acidic soils, in addition to its high biological nitrification inhibition activity. Megathyrsus maximus is characterized by high forage yield and nutritional quality, as well as extensive, abundant, and deep root systems. To generate information on the potential of selected genotypes of U. humidicola and M. maximus to sequester SOC, vegetative propagules of both species were established in a hydroponic system using two contrasting nutrient solutions: an acidic, low-fertility solution and a neutral, high-fertility solution. The dataset includes information on root morphological traits such as root length, diameter, surface area, volume, branching, and number of root tips, as well as data on the proportion of root suberization, determined through image analysis of histochemical cross-sections. The information provided in this dataset is valuable for plant breeding programs focused on sustainable production, as it enables the evaluation of key root traits associated with SOC sequestration and supports the identification of promising genotypes for this purpose. Methodology:Root morphological and anatomical data were obtained from hydroponic experiments conducted at the Alliance Bioversity & CIAT campus in Palmira, Valle del Cauca, Colombia (3°50′38″ N, 76°35′36″ W). Three tropical forage grass genotypes with contrasting root vigor were evaluated for each species: Megathyrsus maximus (high: Pm21_3522; medium: CIAT_16055; low: CIAT_16379) and Urochloa humidicola (high: Bh16b_1618; medium: CIAT_6133; low: CIAT_26146). Plants were grown under two contrasting nutrient solutions: a neutral-pH solution with high nutrient availability and an acidic-pH solution with low nutrient availability, representing typical soil fertility conditions in Colombia. Each genotype was grown with three biological replicates. Root systems were scanned at 600 dpi using an Epson Expression 12000XL scanner, and morphological traits—including total root length, mean diameter, surface area, volume, number of tips, and branching parameters—were quantified using RhizoVision Explorer software. For anatomical and histochemical analyses, root samples were collected from basal, medial, and apical sections, fixed in an acetic acid–ethanol solution (3:1), and transversely sectioned using a Leica VT1000 S vibratome. Sections were stained with Sudan Red 7B to visualize suberization and imaged using a light microscope. Image preprocessing included background removal using the PlantCV and cv2 libraries in Python, followed by binarization. Colorimetric analyses were then conducted using the colordistance library in R. Suberin, identified by red tonalities, and was detected through the integrated use of PlantCV, cv2, matplotlib.pyplot, and NumPy. Ten chromatic clusters were defined per image, and the relative proportion of each cluster was converted into a colorimetric descriptor. This information, combined with the total image area (in pixels), was used to estimate the relative area occupied by suberin.